P-graph approach to optimal operational adjustment in polygeneration plants under conditions of process inoperability - Tan, Raymond Girard R. (Animo Repository, 2014)
Polygeneration plants are inherently more efficient, and generate reduced emissions, in comparison to equivalent stand-alone production systems. These benefits arise from process integration opportunities within the plant. However, such integration also creates interdependencies among process units, which may lead to cascading failures in the event of partial or complete inoperability of key system components. In such cases, the major operational concern is to maximize operating profits (or minimize losses relative to the baseline state) by reallocating process streams; process units may be run at partial load or shut down completely, as needed. In previous work, it has been proposed to determine the optimal operational adjustments using mixed-integer linear programming (MILP). In this note, we propose an alternative methodology for determining the optimal adjustments based on P-graphs, and demonstrate it using a case study. © 2014 Elsevier Ltd.